2013
DOI: 10.1590/s2176-94512013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of midfacial hypoplasia in syndromic and cleft lip and palate patients by means of a rigid external distractor (RED)

Abstract: INTRODUCTION: Distraction Osteogenesis (DO) became an alternative for the treatment of severe craniofacial skeletal dysplasias. The rigid external distraction device (RED) is successfully used to advance the maxilla and all the maxillary-orbital-frontal complex (monobloc) in children, adolescents and adults. This approach provides predictable and stable results, and it can be applied alone or with craniofacial orthognathic surgical procedures. OBJECTIVE: In the present article, the technical aspects relevant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…This approach provides predictable and stable results [12]. This results are the same as ours and proved efficacy of this method.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This approach provides predictable and stable results [12]. This results are the same as ours and proved efficacy of this method.…”
Section: Discussionsupporting
confidence: 86%
“…Also in tumors abalation one can use transport DO [12]. Janardhan reported that Advancement of the anterior maxilla alone without interfering with the velopharyngeal sphincter may be advantageous in cleft patients, who more commonly have speech deficits and dental crowding.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the method used by Engel et al (2019) in their study and by Kuroda et al (2011) in their case. The distraction protocol used was in accordance with the generally advocated activation range of 1-2 mm a day till the skeletal deformity is corrected (Sant'Anna et al, 2013). The RED device is a titanium-based frame with ease of control of vector of distraction (Satoh et al, 2003) and its removal in adults is easier as it can be done without anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, based on that experience, we decided that we needed a distractor that was not submerged underneath the skin for application. 6 Dr. John Polley had experience with neurosurgery, particularly with putting on neurosurgery halos and removing them, as he did during his general surgical rotations, and I was very familiar with the use of the protraction orthodontic face mask. Therefore, we thought about using an external halo as an anchorage point.…”
Section: The Rigid External Device (Red) For Midface Distraction Thatmentioning
confidence: 99%
“…The halo is produced commercially and there are two companies that manufacture it at this time. The system that we originally designed for cleft patients 6 was also used for craniofacial patients. Based on the experience of the baby, we pulled from four points (two supra orbital and two at the dental level through the intraoral splint traction hooks).…”
Section: You Have Been Working With Red For Over 20 Years Along Thesmentioning
confidence: 99%